How is E-Learning-Based Distance Learning Implemented in Elementary Schools? - Faisal Adenan (AL-ISHLAH: Jurnal Pendidikan, 2022)
The Covid-19 pandemic has affected learning activities in Indonesia, including the pattern of elementary school learning activities in the region. The teacher conducts learning with a distance learning system and utilizes e-learning. This study aims to describe distance learning on social studies content carried out by teachers and provide information about the obstacles that occur in the implementation of distance learning based on e-learning. This research is qualitative research with a phenomenological type that describes distance learning activities carried out in elementary schools. Collecting data using interviews, observation and documentation. The data analysis technique uses the theoretical steps of Miles, Huberman and Saldana. Based on the results of the interviews, distance learning was successfully implemented by utilizing the Whatsapp application and the teacher-controlled platform. The results show that distance learning can run according to competence and curriculum. There are obstacles in the implementation of learning, namely the limitations of internet signals, adjustment of learning styles based on e-learning and access to learning platforms in the form of mobile phones which are still limited.